A surfacing flux-cored wire, a method of manufacturing the same, and a welding method
Patent Information
- Application Number
- CN202611204464.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]目前,现有耐磨堆焊药芯焊丝多以高铬合金体系为主,利用铬元素形成的Cr7C3等碳化物实现耐磨性能,但单一高铬体系的药芯焊丝存在明显缺陷:一方面,碳化物相易团聚、分布不均,导致堆焊层韧性较差,在冲击载荷作用下易出现裂纹、剥落现象,难以适应强冲击、高磨损的复杂工况;另一方面,堆焊层的硬度与韧性难以兼顾,若单纯提高铬含量以提升硬度,会进一步降低韧性,反之则会牺牲耐磨性能,无法满足工业设备对堆焊层高耐磨、高韧性、无裂纹的核心需求
本发明的堆焊药芯焊丝通过组分配比实现耐磨与韧性的协同提升:本发明突破现有单一高铬体系的局限,采用高铬-铌钒复合合金体系,合理配比高碳铬铁、铌铁、钒铁的用量,其中,铬元素形成Cr7C3碳化物,奠定堆焊层的耐磨基础;铌、钒元素形成细小弥散的NbC、VC碳化物,其硬度高于Cr7C3,且能有效细化晶粒、抑制Cr7C3碳化物团聚,同时改善堆焊层的韧性,解决了现有高铬药芯焊丝“硬而脆”的技术难题。
Smart Images

Figure CN123000306A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of welding materials technology, and in particular to a flux-cored welding wire for overlay welding, its preparation method, and welding method. Background Technology
[0002] Hardfacing technology is an effective means of strengthening or repairing workpiece surfaces by depositing an alloy layer with specific properties (such as wear resistance, corrosion resistance, and high temperature resistance) onto the workpiece surface through welding. It is widely used in various fields of industrial production. Wear-resistant hardfacing is a major application area of hardfacing technology, and its core lies in the performance of the hardfacing material. Flux-cored welding wire, with its advantages of flexible composition adjustment, high hardfacing efficiency, aesthetically pleasing results, and strong adaptability, has become the mainstream material in the field of wear-resistant hardfacing.
[0003] Currently, most existing wear-resistant flux-cored welding wires are based on high-chromium alloy systems, utilizing chromium to form carbides such as Cr7C3 to achieve wear resistance. However, flux-cored welding wires based on a single high-chromium system have significant drawbacks: on the one hand, the carbide phase is prone to agglomeration and uneven distribution, resulting in poor toughness of the weld overlay. Under impact loads, cracks and spalling are likely to occur, making it difficult to adapt to complex working conditions of strong impact and high wear. On the other hand, it is difficult to balance the hardness and toughness of the weld overlay. Simply increasing the chromium content to improve hardness will further reduce toughness, while conversely, it will sacrifice wear resistance, failing to meet the core requirements of industrial equipment for high wear resistance, high toughness, and crack-free weld overlays. Summary of the Invention
[0004] This invention provides a flux-cored welding wire for overlay welding, its preparation method, and welding method, so as to improve the overall performance of the flux-cored welding wire for overlay welding.
[0005] The present invention provides a flux-cored welding wire for surfacing, comprising a steel strip sheath and a flux core filled within the steel strip sheath. The flux core comprises the following raw materials and their respective mass percentages, based on the total mass of the flux core: high-carbon ferrochrome: 35-45%, ferroniobium: 4-8%, ferrovanadium: 3-6%, graphite: 2-4%, ferromanganese: 5-8%, ferrosilicon: 3-5%, ferrotitanium: 1-2.5%, rare earth ferrosilicon: 0.5-1.5%, slag-forming agent: 8-15%, binder: 1-2%, and the balance being iron powder.
[0006] In one embodiment of the present invention, the high-carbon ferrochrome contains Cr with a mass fraction ≥70%, C with a mass fraction of 6-8%, and impurity content ≤2%; the ferroniobium contains Nb with a mass fraction ≥60%, and impurity content ≤3%; the ferrovanadium contains V with a mass fraction ≥50%, and impurity content ≤3%; the ferromanganese contains Mn with a mass fraction ≥80%, and impurity content ≤2%; the ferrosilicon contains Si with a mass fraction ≥75%, and impurity content ≤2%; the ferrotitanium contains Ti with a mass fraction of 20-35%, and impurity content ≤2%; the rare-earth ferrosilicon contains rare-earth elements (Re+Ce) with a mass fraction ≥46%, Re with a mass fraction of 30-33%, Si with a mass fraction ≤40%, and impurity content ≤3%; the iron powder is reduced iron powder with a purity ≥99%; the graphite has a purity ≥99%; the binder is water glass with a modulus of 2.8-3.2 and a mass concentration of 30-40%.
[0007] In one embodiment of the present invention, the particle size of the high-carbon ferrochrome satisfies ≥95% of the powder passing through 40 mesh, the particle size of the ferroniobium and ferrotitanium satisfies ≥95% of the powder passing through 60 mesh, the particle size of the ferrovanadium, ferrosilicon and ferrosilicon satisfies ≥95% of the powder passing through 80 mesh, the particle size of the ferromanganese satisfies ≥95% of the powder passing through 50 mesh, and the particle size of the iron powder and graphite is 100~150 mesh.
[0008] In one embodiment of the present invention, the slag-forming agent includes alumina, magnesium oxide and calcium oxide, wherein the mass ratio of alumina, magnesium oxide and calcium oxide is 2:1:1, and the particle size of the slag-forming agent is 100~200 mesh.
[0009] In one embodiment of the present invention, the outer sheath of the steel strip is a low-carbon steel strip, and the outer sheath of the steel strip comprises the following components and the mass percentage of each component as follows: C≤0.10%, Si≤0.05%, Mn≤0.50%, P≤0.020%, S≤0.020%, with the balance being Fe.
[0010] In one embodiment of the present invention, the diameter of the flux-cored welding wire is 1.2~2mm.
[0011] In one embodiment of the present invention, the outer skin of the steel strip has a thickness of 1 mm and a width of 14 mm.
[0012] In one embodiment of the present invention, the mass of the flux core is 30-40% of the total mass of the flux-cored welding wire.
[0013] This invention also provides a method for preparing a flux-cored welding wire for overlay welding, comprising the following steps: The raw materials for the drug core are mixed according to the specified ratio, and then thoroughly mixed in a mixer to obtain the drug core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove; The U-shaped groove filled with the flux core is closed and drawn by a wire drawing machine to the required welding wire diameter to obtain the flux-cored welding wire for overlay welding.
[0014] This invention also provides a welding method for surfacing flux-cored welding wire, wherein the shielding gas is CO2, the welding substrate is Q235 steel, and the surfacing process parameters are: welding current of 200~300A, welding voltage of 28~32V, welding speed of 15~20cm / min, interpass temperature controlled below 150℃, and surfacing thickness of 15mm.
[0015] The beneficial effects of this invention are as follows: The flux-cored welding wire proposed in this invention adds ferrotitanium and rare-earth ferrosilicon to the flux core formulation. Ferrotitanium, as a strong deoxidizer, can effectively remove oxygen during the welding process, reducing the oxidation loss of alloying elements. Simultaneously, the formed TiC can further strengthen the weld overlay. The rare-earth elements in the rare-earth ferrosilicon can purify the molten pool, refine the grains, improve the formation of the weld overlay, reduce defects such as porosity and slag inclusions, and simultaneously enhance the bonding strength between the weld overlay and the substrate. Furthermore, the use of a composite slag-forming agent of alumina, magnesium oxide, and calcium oxide instead of traditional fluoride slag-forming agents not only reduces harmful gas emissions, making it more environmentally friendly, but also provides excellent slag-forming effect, effectively protecting the molten pool, avoiding air pollution, and improving the stability of weld overlay quality. Attached Figure Description
[0016] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application. It is obvious that the drawings described below are merely some embodiments of this application, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort.
[0017] In the attached diagram: Figure 1 This is a flowchart illustrating the preparation process of a flux-cored welding wire for overlay welding, as provided in an embodiment of the present invention. Detailed Implementation
[0018] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0019] It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. The drawings only show the components related to the present invention and are not drawn according to the actual number, shape and size of the components in the actual implementation. In the actual implementation, the form, quantity and proportion of each component can be arbitrarily changed, and the layout of the components may also be more complex.
[0020] In the following description, numerous details are explored to provide a more thorough explanation of embodiments of the invention. However, it will be apparent to those skilled in the art that embodiments of the invention may be practiced without these specific details. In other embodiments, well-known structures and devices are shown in block diagram form rather than in detail to avoid obscuring embodiments of the invention.
[0021] In this document, when referring to numerical ranges, unless otherwise specified, the distribution of selectable values within a numerical range is considered continuous, including the two endpoints of the range (i.e., the minimum and maximum values), and every value between these two endpoints. When multiple numerical ranges are provided to describe a feature or property, these numerical ranges can be combined.
[0022] Niobium and vanadium, as important microalloying elements, can form fine and dispersed NbC and VC carbides in metallic materials. These carbides have a higher hardness than Cr7C3 and can effectively refine grains and inhibit carbide agglomeration, thereby improving the material's toughness while enhancing its hardness and wear resistance. However, current technologies for applying niobium and vanadium to high-chromium flux-cored welding wires suffer from problems such as unreasonable element ratios, easy composition loss due to burn-off, and imperfect preparation processes. Either the amount of niobium and vanadium added is too small, failing to fully exert their strengthening effect; or the amount added is too large, leading to poor flux fluidity, easy formation of porosity and slag inclusions during welding, and easy cracking of the weld layer, making it difficult to achieve a synergistic improvement in wear resistance and toughness.
[0023] In addition, the flux core formulations of existing high-chromium flux-cored welding wires often contain a large amount of fluorides and oxides as slag-forming agents and deoxidizers. These substances are prone to generating harmful gases during the welding process, which not only pollute the environment but also reduce the bonding strength between the weld layer and the substrate. At the same time, their manufacturing process often adopts traditional cold rolling and drawing, which is prone to defects such as flux core segregation, uneven wire diameter, and poor bonding between the outer sheath and the flux core, affecting the welding process performance and welding quality stability of the welding wire.
[0024] Therefore, in view of the technical problems of existing high-chromium wear-resistant flux-cored welding wires, such as difficulty in achieving both wear resistance and toughness, severe element loss, imperfect preparation process, and unstable welding quality, this invention provides a flux-cored welding wire to improve the overall performance of flux-cored welding wires.
[0025] The flux-cored welding wire provided by this invention includes a steel strip outer sheath and a flux core filled within the steel strip outer sheath. Based on the total mass of the flux core, the flux core includes the following raw materials and the mass percentage of each raw material: high carbon ferrochrome: 35~45%, ferroniobium: 4~8%, ferrovanadium: 3~6%, graphite: 2~4%, ferromanganese: 5~8%, ferrosilicon: 3~5%, ferrotitanium: 1~2.5%, rare earth ferrosilicon: 0.5~1.5%, slag-forming agent: 8~15%, binder: 1~2%, and the balance is iron powder.
[0026] In one embodiment of the present invention, the high-carbon ferrochrome contains Cr with a mass fraction ≥70%, C with a mass fraction of 6-8%, and impurity content ≤2%; ferroniobium contains Nb with a mass fraction ≥60%, and impurity content ≤3%; ferrovanadium contains V with a mass fraction ≥50%, and impurity content ≤3%; ferromanganese contains Mn with a mass fraction ≥80%, and impurity content ≤2%; ferrosilicon contains Si with a mass fraction ≥75%, and impurity content ≤2%; ferrotitanium contains Ti with a mass fraction of 20-35%, and impurity content ≤2%; ferrosilicon contains rare earth elements (Re+Ce) with a mass fraction ≥46%, Re with a mass fraction of 30-33%, Si with a mass fraction ≤40%, and impurity content ≤3%; the iron powder is reduced iron powder with a purity ≥99%; the graphite has a purity ≥99%; and the binder is water glass (sodium silicate aqueous solution) with a modulus of 2.8-3.2 and a mass concentration of 30-40%.
[0027] In one embodiment of the present invention, the particle size of high-carbon ferrochrome meets the requirement of ≥95% of powder passing through 40 mesh, the particle size of ferroniobium and ferrotitanium meets the requirement of ≥95% of powder passing through 60 mesh, the particle size of ferrovanadium, ferrosilicon and rare earth ferrosilicon meets the requirement of ≥95% of powder passing through 80 mesh, the particle size of ferromanganese meets the requirement of ≥95% of powder passing through 50 mesh, and the particle size of iron powder and graphite is 100~150 mesh.
[0028] In one embodiment of the present invention, the slag-forming agent includes alumina, magnesium oxide and calcium oxide, the mass ratio of alumina, magnesium oxide and calcium oxide is 2:1:1, and the particle size of the slag-forming agent is 100~200 mesh.
[0029] In one embodiment of the present invention, the outer sheath of the steel strip is a low-carbon steel strip, and the chemical composition of the outer sheath of the steel strip by mass percentage is: C≤0.10%, Si≤0.05%, Mn≤0.50%, P≤0.020%, S≤0.020%, with the balance being Fe.
[0030] In one embodiment of the present invention, the diameter of the flux-cored welding wire used for overlay welding is 1.2~2mm.
[0031] In one embodiment of the present invention, the thickness of the steel strip outer skin is 1 mm and the width is 14 mm.
[0032] In one embodiment of the present invention, the mass of the flux core is 30-40% of the total mass of the flux-cored welding wire, that is, the filling rate of the flux-cored welding wire is 30-40%.
[0033] The flux-cored welding wire of the present invention has the following advantages: The flux-cored welding wire of this invention achieves a synergistic improvement in wear resistance and toughness through component ratio: This invention breaks through the limitations of the existing single high-chromium system and adopts a high-chromium-niobium-vanadium composite alloy system, with a reasonable ratio of high-carbon ferrochrome, ferroniobium, and ferrovanadium. Among them, chromium forms Cr7C3 carbide, laying the foundation for the wear resistance of the weld overlay; niobium and vanadium form fine and dispersed NbC and VC carbides, which have a higher hardness than Cr7C3 and can effectively refine the grains and inhibit the agglomeration of Cr7C3 carbide, while improving the toughness of the weld overlay, thus solving the technical problem of existing high-chromium flux-cored welding wires being "hard and brittle".
[0034] The optimized flux core formulation reduces element loss and improves welding process performance: This invention adds ferrotitanium titanate and ferrosilicon rare earth to the flux core formulation. Ferrotitanium titanate, as a strong deoxidizer, effectively removes oxygen during the welding process, reducing the oxidation loss of alloying elements. Simultaneously, the formed TiC further strengthens the weld overlay. The rare earth elements in ferrosilicon purify the molten pool, refine grains, improve the weld overlay formation, reduce defects such as porosity and slag inclusions, and enhance the bonding strength between the weld overlay and the substrate. Furthermore, a composite slag-forming agent of alumina, magnesium oxide, and calcium oxide is used instead of traditional fluoride slag-forming agents, reducing harmful gas emissions and making it more environmentally friendly. It also provides excellent slag-forming effect, effectively protecting the molten pool, preventing air pollution, and improving the stability of weld overlay quality.
[0035] With a wide range of applications and strong practicality, the high-chromium niobium vanadium composite wear-resistant flux-cored welding wire prepared by this invention has a weld layer with high wear resistance, high toughness, no cracks, and high bonding strength. It can be widely used for surface strengthening and repair of easily worn parts such as mining machinery (such as crusher hammers and liners), metallurgical equipment (such as rolls and troughs), and construction machinery (such as excavator bucket teeth and bulldozer blades). It can significantly reduce the wear rate of equipment, reduce the number of maintenance and costs, and improve the service life and operating efficiency of equipment. It has important industrial application value and economic benefits.
[0036] The weld overlay of this invention has the characteristics of high wear resistance, high toughness, and no cracks, and has important industrial application value and market prospects.
[0037] Please see Figure 1 The present invention also provides a method for preparing a flux-cored welding wire for overlay welding, comprising the following steps: S1. Prepare the drug core raw materials according to the formula, and then mix them thoroughly in a mixer to obtain the drug core; S2. Roll the outer skin of the steel strip into a U-shaped groove, and fill the core with the U-shaped groove; S3. The U-shaped groove filled with flux is closed and drawn through a wire drawing machine to the required welding wire diameter to obtain the flux-cored welding wire for overlay welding.
[0038] In step S1, based on the total mass of the core, the core includes the following raw materials and the mass percentage of each raw material: high carbon ferrochrome: 35~45%, ferroniobium: 4~8%, ferrovanadium: 3~6%, graphite: 2~4%, ferromanganese: 5~8%, ferrosilicon: 3~5%, ferrotitanium: 1~2.5%, rare earth ferrosilicon: 0.5~1.5%, slag-forming agent: 8~15%, binder: 1~2%, and the balance is iron powder.
[0039] In step S2, the outer sheath of the steel strip is a low-carbon steel strip, comprising the following components by mass percentage: C≤0.10%, Si≤0.05%, Mn≤0.50%, P≤0.020%, S≤0.020%, with the balance being Fe. For example, the outer sheath has a thickness of 1 mm and a width of 14 mm, and the flux-cored wire filling amount is 30-40% of the total mass of the flux-cored welding wire.
[0040] In step S3, the diameter of the flux-cored welding wire is 1.2~2mm, for example, any value among 1.2mm, 1.5mm, or 2mm or 1.2~2mm.
[0041] The present invention also provides a welding method for surfacing flux-cored welding wire, characterized in that the shielding gas is CO2 and the welding method is used for testing, the welding base is Q235 steel, and the surfacing process parameters are: welding current of 200~300A, welding voltage of 28~32V, welding speed of 15~20cm / min, interpass temperature controlled below 150℃, and surfacing thickness of 15mm.
[0042] The technical solution of the present invention will be described in detail below through several specific embodiments. Unless otherwise stated, the raw materials and reagents used in the following embodiments are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the embodiments are all commercially available.
[0043] Example 1 The raw materials for the core are prepared according to the following ratio: high carbon ferrochrome: 40%, ferroniobium: 6%, ferrovanadium: 4.5%, graphite: 3%, ferromanganese: 6.5%, ferrosilicon: 4%, ferrotitanium: 1.8%, rare earth ferrosilicon: 1%, slag-forming agent: 12%, binder: 1.6%, with the balance being reduced iron powder. The mixture is then thoroughly mixed in a mixer to obtain the core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove with a filling rate of 30%. The U-shaped groove filled with flux is closed and drawn to 1.2mm using a wire drawing machine to obtain the flux-cored welding wire for overlay welding.
[0044] In this embodiment, the outer sheath of the steel strip is a low-carbon steel strip, which includes the following components by mass percentage: C 0.1%, Si 0.05%, Mn 0.5%, P 0.02%, S 0.02%, with the balance being Fe.
[0045] Example 2 The raw materials for the core are prepared according to the following ratio: high carbon ferrochrome: 38%, ferroniobium: 5%, ferrovanadium: 4%, graphite: 2.5%, ferromanganese: 6%, ferrosilicon: 3.5%, ferrotitanium: 1.5%, rare earth ferrosilicon: 0.8%, slag-forming agent: 10%, binder: 1.2%, with the balance being reduced iron powder. The mixture is then thoroughly mixed in a mixer to obtain the core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove with a filling rate of 35%. The U-shaped groove filled with flux is closed and drawn to 1.6mm using a wire drawing machine to obtain the flux-cored welding wire for overlay welding.
[0046] In this embodiment, the outer sheath of the steel strip is a low-carbon steel strip, which includes the following components by mass percentage: C 0.08%, Si 0.04%, Mn 0.4%, P 0.02%, S 0.02%, with the balance being Fe.
[0047] Example 3 The raw materials for the core are prepared according to the following ratio: high carbon ferrochrome: 42%, ferroniobium: 7%, ferrovanadium: 5%, graphite: 3.5%, ferromanganese: 7%, ferrosilicon: 4.5%, ferrotitanium: 2%, rare earth ferrosilicon: 1.2%, slag-forming agent: 13%, binder: 1.8%, with the balance being reduced iron powder. The mixture is then thoroughly mixed in a mixer to obtain the core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove with a filling rate of 40%. The U-shaped groove filled with flux is closed and drawn to 2mm using a wire drawing machine to obtain the flux-cored welding wire for overlay welding.
[0048] In this embodiment, the outer sheath of the steel strip is a low-carbon steel strip, which includes the following components by mass percentage: C 0.09%, Si 0.05%, Mn 0.4%, P 0.02%, S 0.02%, with the balance being Fe.
[0049] Example 4 The raw materials for the core are prepared according to the following ratio: high carbon ferrochrome: 35%, ferroniobium: 8%, ferrovanadium: 6%, graphite: 2%, ferromanganese: 8%, ferrosilicon: 5%, ferrotitanium: 2.5%, rare earth ferrosilicon: 1.5%, slag-forming agent: 8%, binder: 2%, and the balance being reduced iron powder. The mixture is then thoroughly mixed in a mixer to obtain the core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove with a filling rate of 38%. The U-shaped groove filled with flux is closed and drawn to 1.2mm using a wire drawing machine to obtain the flux-cored welding wire for overlay welding.
[0050] In this embodiment, the outer sheath of the steel strip is a low-carbon steel strip, which includes the following components by mass percentage: C 0.1%, Si 0.05%, Mn 0.4%, P 0.01%, S 0.02%, with the balance being Fe.
[0051] Example 5 The raw materials for the core are prepared according to the following ratio: high carbon ferrochrome: 45%, ferroniobium: 4%, ferrovanadium: 3%, graphite: 4%, ferromanganese: 5%, ferrosilicon: 3%, ferrotitanium: 1%, rare earth ferrosilicon: 0.5%, slag-forming agent: 15%, binder: 1%, and the balance being reduced iron powder. The mixture is then thoroughly mixed in a mixer to obtain the core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove with a filling rate of 32%. The U-shaped groove filled with flux is closed and drawn to 1.6mm using a wire drawing machine to obtain the flux-cored welding wire for overlay welding.
[0052] In this embodiment, the outer sheath of the steel strip is a low-carbon steel strip, which includes the following components by mass percentage: C 0.07%, Si 0.05%, Mn 0.4%, P 0.015%, S 0.02%, with the balance being Fe.
[0053] The slag-forming agent in Examples 1 to 5 includes alumina, magnesium oxide and calcium oxide, with a mass ratio of alumina, magnesium oxide and calcium oxide of 2:1:1. The thickness of the steel strip outer skin is 1 mm and the width is 14 mm.
[0054] The mass percentages of each component in the flux-cored wire prepared in Examples 1 to 5 are shown in Table 1. The flux-cored wires prepared in Examples 1 to 5 were subjected to flux-cored welding tests. The substrate was Q235 steel, and CO2 was used as the shielding gas. The welding parameters are shown in Table 2. The test results include mechanical properties, weld overlay properties, and wear resistance. Specifically, the strength and impact properties of the flux-cored wire are shown in Table 3, the hardness and surface quality of the weld overlay are shown in Table 4, and the wear resistance of the weld overlay is shown in Table 5.
[0055] The performance testing methods in this application are as follows: The bonding strength between the weld overlay and the substrate, as well as the impact energy, are tested using the following methods: The bonding strength is tested using a tensile testing machine. A strip sample, 300mm long, 20mm thick, and 25mm wide, is selected from the test specimens and processed into a sheet shape, ensuring the surface condition is correct. Data is collected using a tensile testing machine. The impact energy is tested using an impact testing machine. A 10mm*10mm*55mm sample is taken from the test specimens and processed into a block. A KV2 notch is cut at the center for impact testing. Three blocks are tested as a group, and the average value is taken.
[0056] The test method for the hardness of the weld overlay is as follows: The HRC value of the weld overlay is tested using an HRD-150 Rockwell hardness tester. Specifically, five layers of welding wire are welded to a thickness of 15mm. After the test plate is welded, the bottom surface of the base material and the surface of the weld overlay are processed. First, the bottom surface of the base material is machined with a milling machine to remove the arc caused by deformation during welding. Then, the surface of the weld overlay is machined with a grinding machine to achieve a surface roughness Ra of less than 3.2μm. The hardness measurement points are staggered between the arc initiation and arc termination areas, and the average value is taken after measuring three points.
[0057] The wear resistance of the weld overlay is tested as follows: The wear resistance wear amount is tested using the weighing method, which is a method to determine the wear amount by measuring the weight change of the sample before and after the wear test. First, select a representative sample according to the testing requirements, ensuring its surface is flat, clean, and free of oil, impurities, etc. Second, use a balance to initially weigh the sample and record the initial weight m0. Third, install the sample on the corresponding wear testing machine and conduct a wear test using the same test parameters: load 50N, speed 200r / min, and friction time 2h. Fourth, after the wear test, weigh the sample again using a balance and record the weight m1 after the test. Fifth, the absolute wear amount of a single sample: ΔM = m0 m1; Calculate the absolute wear of the reference sample and the tested sample respectively; Relative wear calculation formula: Relative wear (%) = ×100%.
[0058] Table 1. Components of the flux core in the flux-cored wires prepared in Examples 1 to 5
[0059] Table 2 Welding parameters of the flux-cored welding wires prepared in Examples 1 to 5
[0060] Table 3. Strength and impact properties of the flux-cored welding wires prepared in Examples 1 to 5
[0061] Table 4. Hardness and surface quality of the weld overlay of the flux-cored welding wires prepared in Examples 1 to 5
[0062]
[0063] Table 5. Abrasion resistance of the flux-cored welding wires prepared in Examples 1 to 5 As can be seen from Tables 1 to 5, the flux-cored welding wires prepared in Examples 1-5 of this invention exhibit excellent hardness, impact toughness, and bonding strength of the weld overlay. The hardness of the weld overlay can reach HRC62-68, the room temperature impact energy KV2≥27J, and the relative wear is relatively low. The wear resistance is improved by more than 30% compared with existing high-chromium flux-cored welding wires, and the service life is extended by 2-3 times. The weld overlay is free of cracks, pores, and slag inclusions, with few defects and good weld quality, fully demonstrating that the welding wire of this invention has excellent wear resistance, toughness, and bonding performance.
[0064] In summary, the flux-cored welding wire proposed in this invention reduces element loss and improves welding process performance by optimizing the flux core formulation. This invention adds ferrotitanium and rare-earth ferrosilicon to the flux core formulation. Ferrotitanium, as a strong deoxidizer, effectively removes oxygen during the welding process, reducing the oxidation loss of alloying elements. Simultaneously, the formed TiC further strengthens the weld overlay. The rare-earth elements in the rare-earth ferrosilicon purify the molten pool, refine the grains, improve the weld overlay formation, reduce defects such as porosity and slag inclusions, and enhance the bonding strength between the weld overlay and the substrate. Furthermore, the use of a composite slag-forming agent of alumina, magnesium oxide, and calcium oxide instead of traditional fluoride slag-forming agents not only reduces harmful gas emissions, making it more environmentally friendly, but also provides excellent slag-forming effect, effectively protecting the molten pool, preventing air pollution, and improving the stability of the weld overlay quality.
[0065] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A flux-cored welding wire for overlay welding, characterized in that, The material comprises a steel strip outer sheath and a core filled within the steel strip outer sheath. Based on the total mass of the core, the core comprises the following raw materials and the mass percentage of each raw material: high carbon ferrochrome: 35~45%, ferroniobium: 4~8%, ferrovanadium: 3~6%, graphite: 2~4%, ferromanganese: 5~8%, ferrosilicon: 3~5%, ferrotitanium: 1~2.5%, rare earth ferrosilicon: 0.5~1.5%, slag-forming agent: 8~15%, binder: 1~2%, and the balance being iron powder.
2. The flux-cored welding wire for overlay welding according to claim 1, characterized in that, The high-carbon ferrochrome contains Cr with a mass fraction ≥70%, C with a mass fraction of 6-8%, and impurities ≤2%; the niobium ferrochrome contains Nb with a mass fraction ≥60%, and impurities ≤3%; the vanadium ferrochrome contains V with a mass fraction ≥50%, and impurities ≤3%; the manganese ferrochrome contains Mn with a mass fraction ≥80%, and impurities ≤2%; the silicon ferrosilicon contains Si with a mass fraction ≥75%, and impurities ≤2%; the titanium ferrometallurgical contains Ti with a mass fraction of 20-35%, and impurities ≤2%; the rare earth silicon ferrosilicon contains rare earth elements (Re+Ce) with a mass fraction ≥46%, Re with a mass fraction of 30-33%, Si with a mass fraction ≤40%, and impurities ≤3%; the iron powder is reduced iron powder with a purity ≥99%; the graphite has a purity ≥99%; the binder is water glass with a modulus of 2.8-3.2 and a mass concentration of 30-40%.
3. The flux-cored welding wire according to claim 1, characterized in that, The high-carbon ferrochrome has a particle size of ≥95% passing through a 40-mesh screen; the ferroniobium and ferrotitanium have a particle size of ≥95% passing through a 60-mesh screen; the ferrovanadium, ferrosilicon, and rare earth ferrosilicon have a particle size of ≥95% passing through an 80-mesh screen; the ferromanganese has a particle size of ≥95% passing through a 50-mesh screen; and the iron powder and graphite have a particle size of 100-150 mesh.
4. The flux-cored welding wire according to claim 1, characterized in that, The slag-forming agent comprises alumina, magnesium oxide, and calcium oxide, wherein the mass ratio of alumina, magnesium oxide, and calcium oxide is 2:1:1, and the particle size of the slag-forming agent is 100-200 mesh.
5. The flux-cored welding wire for overlay welding according to claim 1, characterized in that, The outer sheath of the steel strip is a low-carbon steel strip, and based on the mass percentage of the outer sheath, it includes the following components and the mass percentage of each component: C≤0.10%, Si≤0.05%, Mn≤0.50%, P≤0.020%, S≤0.020%, with the balance being Fe.
6. The flux-cored welding wire according to claim 1, characterized in that, The diameter of the flux-cored welding wire used for overlay welding is 1.2~2mm.
7. The flux-cored welding wire according to claim 1, characterized in that, The outer sheath of the steel strip is 1 mm thick and 14 mm wide.
8. The flux-cored welding wire for overlay welding according to claim 1, characterized in that, The mass of the flux core is 30-40% of the total mass of the flux-cored welding wire used for welding.
9. A method for preparing a flux-cored welding wire according to any one of claims 1 to 8, characterized in that, Includes the following steps: The raw materials for the drug core are mixed according to the specified ratio, and then thoroughly mixed in a mixer to obtain the drug core. The outer sheath of the steel strip is rolled into a U-shaped groove, and the core is filled into the U-shaped groove. The U-shaped groove filled with the flux core is closed and drawn by a wire drawing machine to the required welding wire diameter to obtain the flux-cored welding wire for overlay welding.
10. A welding method for a flux-cored welding wire according to any one of claims 1 to 8, characterized in that, The welding process was tested using CO2 as the shielding gas. The base material was Q235 steel. The welding process parameters were as follows: welding current 200~300A, welding voltage 28~32V, welding speed 15~20cm / min, interpass temperature controlled below 150℃, and weld thickness 15mm.
